2010
DOI: 10.1007/s11626-010-9369-0
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial–mesenchymal transition of rat peritoneal mesothelial cells via Rhoa/Rock pathway

Abstract: The objective of this study was to investigate the role of the RhoA/Rock signaling pathway in the epithelial-mesenchymal transition (EMT) of rat peritoneal mesothelial cells (RPMCs). Primary SD rat peritoneal mesothelial cells were cultured in vitro. RPMCs were randomly assigned to four groups: group A (control), group B (TGF-β1, 10 μg/L), group C (10 μg/L TGF-β1 + 10 μmol/L Y-27632, an inhibitor of Rock that was pre-applied for 2 h before TGF-β1 stimulation), and group D (Y-27632 alone, 10 μmol/L). Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
(17 reference statements)
1
20
0
Order By: Relevance
“…43,47 Similarly, activation of downstream effectors of CXCR4, including Rho-GTPases, was observed during EMT and promoted cell movement and migration. [48][49][50] We have shown previously that downstream effectors of CXCR4, RhoGTPases, were up-regulated in MM compared with normal plasma cells and play key roles in the movement, migration, and homing of MM cells to the BM. 7 In addition to the findings that circulating MM cells displayed hypoxic MM features, such as decreased expression of E-cadherin and increased expression of CXCR4, we investigated the role of exposure to a normoxic environment on the behavior of hypoxic cells.…”
Section: Discussionmentioning
confidence: 99%
“…43,47 Similarly, activation of downstream effectors of CXCR4, including Rho-GTPases, was observed during EMT and promoted cell movement and migration. [48][49][50] We have shown previously that downstream effectors of CXCR4, RhoGTPases, were up-regulated in MM compared with normal plasma cells and play key roles in the movement, migration, and homing of MM cells to the BM. 7 In addition to the findings that circulating MM cells displayed hypoxic MM features, such as decreased expression of E-cadherin and increased expression of CXCR4, we investigated the role of exposure to a normoxic environment on the behavior of hypoxic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that RhoA and its downstream kinase Rho-kinase (ROCK) are able to mediate matrix elaboration via mesangial cells (MCs) in hyperglycemic and DN conditions (4,11), and the RhoA/ROCK signaling pathway has been demonstrated to be associated with fibrosis progression in multiple organs including the kidneys, liver and lungs (4,9,12). Furthermore, RhoA/ROCK was previously reported to be associated with EMT (7,13), which was prevented by inhibition of RhoA activation in rat peritoneal cells (13). A previous study by the present authors also revealed that transforming growth factor (TGF)-β1-mediated RhoA/ROCK activation contributed to the dissolution of tight junctions during EMT in HK-2 cell in vitro (14).…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that RhoA is activated by TGF-β1 and is part of an important signaling pathway in TGF-β1-induced EMT (11,12). ROCK is a characteristic, downstream protein in the Rho signaling pathway and an important kinase involved in the regulation of cell movement and cytoskeletal organization (19)(20)(21).…”
Section: Discussionmentioning
confidence: 93%
“…Our previous study revealed that TGF-β1 induced the downregulation of vimentin (a cytoskeletal protein) and the upregulation of α-SMA via the RhoA/ROCK signaling pathway in RPMCs (12). Other stueis, however, have shown that the Rho/ROCK signaling pathway may also mediate the downregulation of claudin-4, which is a component of TJs in corneal, gastric epithelial and Madin-Darby canine kidney epithelial cells (26)(27)(28), indicating that the Rho/ROCK signaling pathway may play a role in the dissolution of TJs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation